Campaign spending in the local government elections of 1999 - BENOIT, Kenneth (Institutional Knowledge at Singapore Management University, 2003)
For the first time in Irish electoral history, the 1999 local elections required candidates to publicly declare their campaign expenditures. Drawing on these data, we explore patterns in campaign spending and assess their impact, both on candidate success and on turnout. First, examining the elections contested by 1,838 candidates from 180 local constituencies and 34 councils, we identify both partisan and geographic spending patterns, and examine how well these can be explained as a function of political and demographic variables. Second, we model and estimate the effects of expenditure on individual electoral outcomes. The findings clearly indicate that even at the relatively miniscule spending levels found in Irish local elections, spending is positively and significantly related to electoral success. Finally, we explore the impact of expenditure on overall turnout and find a clear positive effect of per capita expenditure on turnout.